2022
DOI: 10.3390/buildings12091474
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Seismic Performance of a Steel-Concrete Wind Turbine Tower with the Tuned Mass Damper

Abstract: To optimize the seismic performance of a new type of steel-concrete tower, a 120 m steel-concrete composite tower model with a tuned mass damper (TMD) was constructed in ABAQUS for simulation analysis. Firstly, a time history analysis was conducted to study the towers with and without a TMD to determine the difference in their accelerations, velocities, and displacements. Then, a frequency spectrum analysis was performed to determine the tower vibration reduction effect of TMDs with different mass ratios. Five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…As an important renewable energy source, wind turbine technology has been a signifcant contributor to the world energy production because of its feasible production cost, reliability, and efciency [1]. To meet the increasing energy needs, the steel large-megawatt wind turbines have broadly built in the wind feld at the higher altitudes [2]. However, the steel wind turbine tower (WTT) belongs a typical steel structure with light-damping and long-period, and this means that it will sufer from the excessive vibrations induced by the wind loads [3].…”
Section: Introductionmentioning
confidence: 99%
“…As an important renewable energy source, wind turbine technology has been a signifcant contributor to the world energy production because of its feasible production cost, reliability, and efciency [1]. To meet the increasing energy needs, the steel large-megawatt wind turbines have broadly built in the wind feld at the higher altitudes [2]. However, the steel wind turbine tower (WTT) belongs a typical steel structure with light-damping and long-period, and this means that it will sufer from the excessive vibrations induced by the wind loads [3].…”
Section: Introductionmentioning
confidence: 99%
“…For underground structures, it is widely believed that the displacement and amplitude produced by underground structures under earthquake action are relatively smaller than those of surface structures due to the restraint of the surrounding soil, and the seismic action on underground structures will be smaller than that on surface structures, so people pay less attention to the seismic resistance of underground structures. Most of the existing studies have focused on the seismic resistance of surface structures [16][17][18][19][20]. However, the large earthquakes that have occurred in recent years have shown that underground structures can also be severely damaged when subjected to strong ground motions, and many studies have investigated the damage patterns of tunnel structures during seismic events [21][22][23][24][25], and the issue of seismic damage to underground building structures is gradually gaining attention.…”
Section: Introductionmentioning
confidence: 99%